Extracorporeal Membrane Oxygenation: Advances in Therapy 2016
DOI: 10.5772/64267
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Theoretical Considerations for ECMO System Development

Abstract: Extracorporeal membrane oxygenation (ECMO) is a well-established therapy for the temporary substitution for the heart and/or lungs in patients with acute cardiac or pulmonary failure. Recently, the development of portable systems has allowed for implementation of therapy outside of the intensive care units. ECMO can even be initiated in out-of-hospital situations to allow for patient stabilization and subsequent transfer to an appropriate hospital. This chapter will focus on the authors' development of a perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In patients with COVID-19-unrelated ARDS, extracorporeal membrane oxygenation (ECMO) can be resorted to as a rescue therapy, allowing for temporary replacement of lung and/or heart function with artificial analogs in cardiac or pulmonary failure refractory to conventional clinical treatment [ 13 ]. The evidence collected so far in the literature has yielded mixed results, but several studies [ 14 , 15 ] have reported a survival rate in patients with COVID-19-related ARDS treated with ECMO not lower compared to those with COVID-19-unrelated ARDS [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with COVID-19-unrelated ARDS, extracorporeal membrane oxygenation (ECMO) can be resorted to as a rescue therapy, allowing for temporary replacement of lung and/or heart function with artificial analogs in cardiac or pulmonary failure refractory to conventional clinical treatment [ 13 ]. The evidence collected so far in the literature has yielded mixed results, but several studies [ 14 , 15 ] have reported a survival rate in patients with COVID-19-related ARDS treated with ECMO not lower compared to those with COVID-19-unrelated ARDS [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While patient selection is a critical aspect of ECMO therapy, determining the type of therapy to initiate and how is likewise paramount. In the previous text, some of the topics related to cannulation techniques [7] and pump/circuit design and development were addressed [8]. The chapter by Borrelli further elaborates on these technical aspects of pump/circuit design by outlining their 23-year experience with pump positioning and holder systems.…”
Section: Introductionmentioning
confidence: 99%